1995
DOI: 10.1096/fasebj.9.5.7896017
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of osteocytes to biomechanical stress in vitro

Abstract: It has been known for more than a century that bone tissue adapts to functional stress by changes in structure and mass. However, the mechanism by which stress is translated into cellular activities of bone formation and resorption is unknown. We studied the response of isolated osteocytes derived from embryonic chicken calvariae to intermittent hydrostatic compression as well as pulsating fluid flow, and compared their response to osteoblasts and periosteal fibroblasts. Osteocytes, but not osteoblasts or peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
486
1
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 707 publications
(514 citation statements)
references
References 11 publications
17
486
1
10
Order By: Relevance
“…eNOS global knockout animals exhibit lower BMD, bone formation, and osteoblast activity; with little to no effect on bone resorption, suggesting NO may be important for osteoblast function 49, 50. Previous research shows NO synthesis is induced in osteoblasts and osteocytes by mechanical strain and shear stress 51, 52, 53, 54.…”
Section: Discussionmentioning
confidence: 99%
“…eNOS global knockout animals exhibit lower BMD, bone formation, and osteoblast activity; with little to no effect on bone resorption, suggesting NO may be important for osteoblast function 49, 50. Previous research shows NO synthesis is induced in osteoblasts and osteocytes by mechanical strain and shear stress 51, 52, 53, 54.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocytes are the most abundant cell type in bone. Their location, embedded in the mineralized bone tissue, and demonstrated mechanosensitivity suggest they function as cellular mechanotransducers (5,23). Furthermore, recent studies have shown that osteocytes can support osteoclast formation and activation by direct cell-cell contact with osteoclast precursors (10,60).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the microarchitecture of the bone tissue could serve to indirectly (fluid pressure through cannaliculi) or directly (strain amplification via the lacunae) amplify the strain signal. While some have suggested that osteocytes might be more sensitive to shear than, for instance, transient pressure (Klein-Nulend et al, 1995), there are divergent opinions: e.g., substrate strain prevents osteocyte apoptosis (Plotkin et al, 2005). Recently Han and coworkers have developed a 3D model for the osteocyte process and used large-deformation "elastica" theory to predict the deformed shape of the cell (Han et al, 2004).…”
Section: Mechanosensitive Bone Cellsmentioning
confidence: 99%